Kombinasi Massage Effleurage Olive Oil dan Aromaterapi Diffuser Lavender terhadapTingkat Nyeri dan Kenyamanan pada Persalinan Kala I - Sumiati, Yeti; Suryati, Yayat; Murtiningsih, Murtiningsih; Trisyani, Mira; Hidayat, Monna Maharani (Journal of Telenursing (JOTING), 2025)
This study aimed to determine the effect of a combination of olive oil effleurage massage and lavender diffuser aromatherapy on reducing pain and increasing comfort during the first stage of labor, compared to the pursed lip breathing technique and lavender diffuser aromatherapy. The method used was a quasi-experimental design with a non-equivalent pre-test and post-test with a control group design. The results showed a difference in the mean pain scale between the pre-test and post-test results, with the intervention group experiencing a greater reduction in pain than the control group and the mean comfort level. The Wilcoxon test yielded a p-value of 0.00, indicating that both interventions could reduce labor pain and increase comfort. The Mann-Whitney test yielded a p-value of 0.00, indicating a significant difference in pain and comfort levels in the intervention group compared to the control group. In conclusion, the combination of olive oil effleurage massage, lavender diffuser aromatherapy, and pursed lip breathing can help mothers reduce first-stage labor pain and increase comfort.   Keywords: Aromatherapy, Effleurage, Comfort, Pain, Labor